2013
DOI: 10.1111/rda.12242
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Blood Flow of the Preovulatory Follicle to its Diameter and Endocrine Profile in Dairy Buffalo

Abstract: Blood flow of the preovulatory follicle (POF) wall can be used as a predictor of the quality of POF. Our aim was to determine the correlation of blood flow of POF with the POF diameter, and intra-follicular and plasma concentrations of Insulin-like Growth Factor-I (IGF-1) and oestradiol in dairy buffalo. Nine Murrah buffalo subjected to an ovulation synchronization protocol (Ovsynch) were assessed on day 10 of the protocol for diameter and blood flow of POF, followed by the aspiration of follicle fluid. Prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
5
1
Order By: Relevance
“…This may be due to failure of assay kits used to detect actual hormone or some other unknown reasons. The values of estradiol reported by Varughese et al (2014) and Jerome et al (2016) were lower than the present findings. However, an unique peak and basal profile expected over a normal estrous cycle was not observed in the present study due to multiple injection of GnRH and PG at various intervals.…”
Section: Hormonal Profilecontrasting
confidence: 83%
“…This may be due to failure of assay kits used to detect actual hormone or some other unknown reasons. The values of estradiol reported by Varughese et al (2014) and Jerome et al (2016) were lower than the present findings. However, an unique peak and basal profile expected over a normal estrous cycle was not observed in the present study due to multiple injection of GnRH and PG at various intervals.…”
Section: Hormonal Profilecontrasting
confidence: 83%
“…Recently, we did report moderate (r = 0.46 -0.58) correlations between POF diameter and blood flow, albeit without follicle categorization (de Tarso et al, 2015). Contradicting results were found in dairy buffalos (Varughese et al, 2014), where larger follicles (>16 mm) had lower follicle wall blood flow when compared with smaller follicles. The former study also obtained a weak Pearson correlation coefficient (r = 0.21) between POF diameter and blood flow using the pixel counting technique, which supports the current pixel data findings.…”
Section: Discussionmentioning
confidence: 56%
“…The positive aspects of a greater blood flow supply and the importance of the maintenance of an appropriate vasculature around the follicle have been studied during the periods of follicle selection and dominance (Acosta et al, 2005;Miura et al, 2014), and also during the preovulatory phase in different species (Brannstorm et al, 1998;Acosta et al, 2003;Gastal et al, 2006;Elsherry et al, 2010;Varughese et al, 2014). Considering that a larger follicle size is associated with a greater follicle blood flow, it is reasonable to assume that a greater blood flow around the follicle might be essential and significant in predicting follicle and oocyte fertility (Huey et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A positive correlation was noticed between the follicle size at the time of AI (SaFilho et al, 2010) and corpus luteum size (Baruselli et al, 2003) after AI with pregnancy rate in cows. Varughese et al (2014) observed that Doppler study proved to be better for accurate determination of quality of the follicle and to classify the CL as active or regressing in cows. Although, buffaloes are mainstay of the dairy industry in South and South East Asia, unlike the study in cows, little attention has been devoted in buffaloes on the haemodynamics of ovarian follicle and its relationship to serum steroid profiles and conception rate following AI at natural and induced estrus.…”
Section: Introductionmentioning
confidence: 99%